High-compaction phosphate positive electrode material as well as preparation method and application thereof

By refining the slurry of different particle size and mixing according to a specific proportion, it is difficult to take into account the problem of high -voltage density density, comparison capacity, and cycle stability.

CN119370819APending Publication Date: 2025-01-28PHYLION-QINGYUAN (SICHUAN) NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411502778.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

It is difficult for phosphate cathode materials to take into account high compaction density, specific capacity and cycle stability.

Method used

By mixing the raw materials to form initial pulp, and refine it to obtain a different particle size slurry, mix it according to a specific proportion, and then dry and sinter.

Benefits of technology

Activirus of phosphate positive material has both high -voltage density, higher discharge ratio capacity and good circulatory performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370819A_ABST
    Figure CN119370819A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrolyte material preparation, in particular to a phosphate positive electrode material and a preparation method and application thereof. According to the invention, the initial slurry formed by the raw materials is refined to obtain four kinds of slurry with different particle size distribution, the four kinds of slurry are mixed according to a specific proportion and then dried to obtain dry particles with mismatched sizes, and then the dry particles are sintered to form the phosphate positive electrode material with appropriate particle size distribution. After being pressed, the composite material has relatively high compaction density, relatively high discharge gram capacity and relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrolyte material preparation, and in particular to a phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] As the world's urgent demand for environmental protection and renewable energy continues to intensify, the importance of lithium batteries as an efficient and clean energy storage and conversion device has become increasingly prominent. Lithium batteries not only meet people's pursuit of clean energy, but also greatly promote the rapid development of electric vehicles, smart grids, portable electronic devices and large-scale energy storage systems. In this context, the technological innovation and breakthrough of positive electrode materials, as the cornerstone of lithium battery performance, are particularly critical. As the core support for lithium battery performance, the technological progress of positive electrode materials is directly related to key indicators such as battery energy density, cycle life and safety. As a commonly used positive electrode material, phosphate positive electrode material usually has high energy density, good cycle stability and safety.

[0003] However, in the related art, it is difficult for phosphate positive electrode materials to have high compaction density, specific capacity and cycle stability. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of phosphate positive electrode materials in the related art that it is difficult to take into account high compaction density, specific capacity and cycle stability, thereby providing a phosphate positive electrode material and its preparation method and application.

[0005] The present invention provides a method for preparing a phosphate positive electrode material, comprising the following steps:

[0006] Mixing raw materials and solvent to form an initial slurry; refining the initial slurry to obtain a first slurry, a second slurry, a third slurry, and a fourth slurry; wherein the raw materials include a metal source and a phosphorus source;

[0007] The first slurry, the second slurry, the third slurry and the fourth slurry are mixed to obtain a mixed slurry, and then dried and sintered to obtain the phosphate positive electrode material;

[0008] Among them, the particle size D1 of the first slurry 50 20-80nm; the particle size D2 of the second slurry 50 100-150nm; the particle size D3 of the third slurry 50 180-350nm; the particle size D4 of the fourth slurry 50 400-500nm;

[0009] The mass percentage of the first slurry in the mixed slurry is m1: 3-5%, the mass percentage of the second slurry in the mixed slurry is m2: 10-12%, the mass percentage of the third slurry in the mixed slurry is m3: 56-65%, and the mass percentage of the fourth slurry in the mixed slurry is m4: 20-27%; and the mass percentages of each slurry satisfy the following relationship: m1+m2+m3+m4=100%.

[0010] It is understandable that D1 in this application 50 、D2 50 、D3 50 、D4 50 The numbers 1, 2, 3, and 4 are only used to distinguish different slurries. 50 、D2 50 、D3 50 、D4 50 The meanings of each are particle size D50.

[0011] Optionally, the refining process is performed by a sand mill.

[0012] Preferably, the raw material further comprises a carbon source;

[0013] Preferably, the metal source includes a transition metal source and an alkali metal source;

[0014] Preferably, the transition metal source comprises an iron source;

[0015] Preferably, the transition metal source includes an iron source and a manganese source;

[0016] Preferably, the alkali metal source is selected from a lithium source or a sodium source.

[0017] Preferably, the mass percentage of each slurry satisfies the following relationship:

[0018] -0.1≤1.1*m3-9*m1-2*m2-0.6*m4≤0.12;

[0019] Further preferably, the mass percentage of each slurry satisfies the following relationship:

[0020] -0.05≤1.1*m3-9*m1-2*m2-0.6*m4≤0.05.

[0021] Preferably, the phosphorus source is selected from at least one of iron phosphate, lithium dihydrogen phosphate, lithium phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid;

[0022] Preferably, the iron source is selected from at least one of ferric phosphate, ferric oxide, ferrous oxalate, iron powder, and ferric nitrate;

[0023] Preferably, the manganese source is selected from at least one of manganese carbonate, manganese oxalate, manganous acetate, manganese dioxide, manganese hydroxide, manganese sulfate, and manganese tetraoxide;

[0024] Preferably, the carbon source is selected from at least one of acetylene black, Ketjen black, graphene, glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, and polyaniline;

[0025] Preferably, the lithium source is selected from at least one of lithium dihydrogen phosphate, lithium nitrate, lithium carbonate, lithium phosphate, lithium hydroxide or lithium acetate;

[0026] Preferably, the sodium source is selected from sodium carbonate 、 At least one of sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium acetate, sodium citrate, and sodium sulfate;

[0027] Preferably, the mass ratio of the carbon element in the carbon source to the phosphorus element in the phosphorus source in the raw material is (0.05-0.7:1).

[0028] Optionally, the phosphoric acid has a purity of 80-90%.

[0029] Preferably, the concentration of the raw material in the initial slurry is 10-70 g / L;

[0030] Preferably, the solvent is selected from water, ethanol or methanol.

[0031] Preferably, the drying is spray drying.

[0032] Preferably, the sintering temperature is 400-900°C and the sintering time is 4-30;

[0033] Preferably, the heating rate during the sintering process is 1-5°C / min.

[0034] Optionally, the sintering atmosphere is a protective gas atmosphere or a reducing gas atmosphere;

[0035] Optionally, the protective gas is selected from at least one of nitrogen, argon, helium and carbon dioxide;

[0036] Optionally, the reducing gas is selected from at least one of carbon monoxide and hydrogen.

[0037] Preferably, the mass ratio of the first slurry, the second slurry, the third slurry and the fourth slurry in the mixed slurry is 3:12:60:25.

[0038] Preferably, the phosphate positive electrode material is lithium iron manganese phosphate, lithium iron phosphate, sodium iron phosphate or sodium iron pyrophosphate.

[0039] Optionally, the phosphate positive electrode material is lithium manganese iron phosphate, wherein the molar ratio of the phosphorus source, the iron source, the manganese source, and the lithium source in the raw material is (1-1.05): (0.1-0.9): (0.1-0.9): (1-1.07);

[0040] Optionally, the phosphate positive electrode material is lithium iron phosphate, wherein the molar ratio of the phosphorus source, the iron source, and the lithium source in the raw material is (1-1.05): (0.92-1): (1-1.07);

[0041] Optionally, the phosphate positive electrode material is sodium iron phosphate, wherein the ratio of phosphorus source, iron source and sodium source in the raw material is (1-1.05): (0.92-1): (1-1.07);

[0042] Optionally, the phosphate positive electrode material is sodium iron pyrophosphate, wherein the mass ratio of phosphorus source, iron source and sodium source in the raw material is (2-2.03): (0.97-1): (2-2.07).

[0043] The present invention also provides a phosphate positive electrode material, including the phosphate positive electrode material prepared by the above-mentioned preparation method.

[0044] The present invention also provides a battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet is made of the above-mentioned phosphate positive electrode material.

[0045] The technical solution of the present invention has the following advantages:

[0046] The preparation method of the phosphate positive electrode material provided by the present invention comprises the following steps: mixing raw materials and a solvent to form an initial slurry; refining the initial slurry to obtain a first slurry, a second slurry, a third slurry and a fourth slurry respectively; wherein the raw materials include a metal source and a phosphorus source; mixing the first slurry, the second slurry, the third slurry and the fourth slurry to obtain a mixed slurry, and then drying and sintering to obtain the phosphate positive electrode material; wherein the particle size of the first slurry is 20-80nm; the particle size of the second slurry is 100-150nm; the particle size of the third slurry is 180-350nm; the particle size of the fourth slurry is 400-500nm; the mass percentage m1 of the first slurry in the mixed slurry is: 3-5%, the mass percentage m2 of the second slurry is: 10-12%, the mass percentage m3 of the third slurry is: 56-65%, and the mass percentage m4 of the fourth slurry is: 20-27%; and the mass percentages of the slurries satisfy the following relationship:

[0047] m1+m2+m3+m4=100%.

[0048] The invention refines the initial slurry formed by the raw materials to obtain four slurries with different particle size distributions, which are mixed in a specific ratio and dried to obtain dry particles with mismatched sizes, which are then sintered to form a phosphate positive electrode material with a suitable particle size distribution, which can have a higher compaction density, a higher discharge gram capacity and better cycle performance after being pressed;

[0049] Further, when the mass percentage of each slurry satisfies the following relationship:

[0050] -0.05≤1.1*m3-9*m1-2*m2-0.6*m4≤0.05;

[0051] The value corresponding to 1.1*m3-9*m1-2*m2-0.6*m4 is too small, there are more small particles, low compaction, and low capacity retention rate; the value corresponding to 1.1*m3-9*m1-2*m2-0.6*m4 is too large, there are more large particles, and the capacity is low; only the phosphate positive electrode material prepared within a specific range has a higher compaction density, higher discharge gram capacity and better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0053] Figure 1 is a scanning electron microscope image of a dried product formed by spray drying in Example 1 of the present invention;

[0054] Figure 2 This is a scanning electron microscope image of the lithium manganese iron phosphate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0055] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0057] The purity of phosphoric acid used in Examples and Comparative Examples was 85%.

[0058] Example 1

[0059] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method comprises the following steps:

[0060] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid (purity of 85%), 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was divided into four groups, and then finely treated by a sand mill to obtain a particle size D1 50 The first slurry is 50nm; the particle size D2 50 The second slurry is 130nm; particle size D3 50 The third slurry is 280nm; particle size D4 50 A fourth slurry of 450 nm;

[0061] The first slurry, the second slurry, the third slurry and the fourth slurry were weighed according to the mass ratio of Table 1; mixed according to the mass ratio of 3:12:60:25, and then spray-dried to form a dry product (the dry product is as shown in FIG. Figure 1 The dried product was heated to 740°C at a heating rate of 2°C / min and sintered in a nitrogen atmosphere at this temperature for 8h to obtain the lithium manganese iron phosphate material (the finished product is shown in Figure 2 shown).

[0062] Example 2

[0063] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method comprises the following steps:

[0064] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid, 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 20nm; the particle size D2 50 The second slurry is 150nm; particle size D3 50 The third slurry is 180nm; particle size D4 50The fourth slurry is 410nm; the first slurry, the second slurry, the third slurry and the fourth slurry are weighed according to the mass proportion in Table 1; they are mixed in a mass ratio of 3:12:60:25, and then spray-dried to form a dry product, the dry product is heated to 740°C at a heating rate of 2°C / min, and sintered in a nitrogen atmosphere at this temperature for 8h to obtain the lithium manganese iron phosphate material.

[0065] Example 3

[0066] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method comprises the following steps:

[0067] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid, 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 80nm; the particle size D2 50 The second slurry is 100nm; particle size D3 50 The third slurry is 340nm; particle size D4 50 A fourth slurry with a particle size of 420 nm; weigh the first slurry, the second slurry, the third slurry and the fourth slurry according to the mass ratio in Table 1; mix them in a mass ratio of 3:12:60:25, and then form a dry product by spray drying, heat the dry product to 740°C at a heating rate of 2°C / min, and sinter in a nitrogen atmosphere at this temperature for 8 to obtain the lithium manganese iron phosphate material.

[0068] Example 4

[0069] This embodiment provides a lithium iron phosphate material, the chemical formula of which is LiFePO4. The preparation method comprises the following steps:

[0070] According to the stoichiometric ratio, 95.60 g of iron phosphate, 24.12 g of lithium carbonate, 10 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 30nm; the particle size D2 50 The second slurry is 100nm; particle size D3 50 The third slurry is 190nm; particle size D4 50A fourth slurry with a thickness of 400nm; weigh the first slurry, the second slurry, the third slurry and the fourth slurry according to the mass proportion in Table 1; mix them in a mass ratio of 3:12:60:25, and then form a dry product by spray drying, heat the dry product to 770°C at a heating rate of 2°C / min, and sinter in a nitrogen atmosphere at this temperature for 8h to obtain the lithium manganese iron phosphate material.

[0071] Example 5

[0072] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 5:10:55:30.

[0073] Example 6

[0074] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 3:12:65:20.

[0075] Example 7

[0076] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry and the fourth slurry are mixed in a mass ratio of 4:10:62:24.

[0077] Example 8

[0078] This embodiment provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 5:12:60:23.

[0079] Comparative Example 1

[0080] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method comprises the following steps:

[0081] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid, 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 500nm; the particle size D2 50 The second slurry is 1300nm; particle size D3 50 The third slurry is 2800nm; particle size D4 50 The fourth slurry is 4500nm; the first slurry, the second slurry, the third slurry and the fourth slurry are weighed according to the mass proportion in Table 1; they are mixed in a mass ratio of 3:12:60:25, and then spray-dried to form a dry product, the dry product is heated to 740°C at a heating rate of 2°C / min, and sintered in a nitrogen atmosphere at this temperature for 8h to obtain the lithium manganese iron phosphate material.

[0082] Comparative Example 2

[0083] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 3:25:60:12.

[0084] Comparative Example 3

[0085] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 1-x Fe x The PO4 preparation method comprises the following steps:

[0086] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid, 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 90nm; the particle size D2 50 The second slurry is 280nm; particle size D3 50 The third slurry is 450nm; the first slurry, the second slurry, the third slurry and the fourth slurry are weighed according to the mass ratio of Table 1; they are mixed in a mass ratio of 15:60:25, and then spray-dried to form a dry product, the dry product is heated to 740°C at a heating rate of 2°C / min, and sintered in a nitrogen atmosphere at this temperature for 8h to obtain the lithium manganese iron phosphate material.

[0087] Comparative Example 4

[0088] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 3:12:25:60.

[0089] Comparative Example 5

[0090] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 12:3:60:25.

[0091] Comparative Example 6

[0092] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of lithium iron manganese phosphate is LiMn 0.6 Fe 0.4 The PO4 preparation method is similar to that of Example 1, except that the first slurry, the second slurry, the third slurry, and the fourth slurry are mixed in a mass ratio of 25:3:12:60.

[0093] Comparative Example 7

[0094] The comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method comprises the following steps:

[0095] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid, 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 10nm; the particle size D2 50 The second slurry is 50nm; particle size D3 50 The third slurry is 130nm; particle size D4 50 A fourth slurry with a particle size of 280 nm; weigh the first slurry, the second slurry, the third slurry and the fourth slurry according to the mass proportion in Table 1; mix them in a mass ratio of 3:12:60:25, and then form a dry product by spray drying, heat the dry product to 740°C at a heating rate of 2°C / min, and sinter in a nitrogen atmosphere at this temperature for 8 hours to obtain the lithium manganese iron phosphate material.

[0096] Comparative Example 8

[0097] This comparative example provides a lithium iron manganese phosphate material, the chemical formula of which is LiMn 0.6 Fe 0.4 The PO4 preparation method comprises the following steps:

[0098] According to the stoichiometric ratio, 29.10 g of manganese tetraoxide, 38.37 g of iron phosphate, 24.20 g of lithium carbonate, 43.99 g of phosphoric acid, 12 g of glucose and water were fully mixed to form an initial slurry with a concentration of 40 g / L; the initial slurry was then refined by a sand mill to obtain a particle size of D1 50 The first slurry is 130nm; the particle size D2 50 The second slurry is 280nm; particle size D3 50 The third slurry is 450nm; particle size D4 50 A fourth slurry with a diameter of 850nm; weigh the first slurry, the second slurry, the third slurry and the fourth slurry according to the mass proportion in Table 1; mix them in a mass ratio of 3:12:60:25, and then form a dry product by spray drying, heat the dry product to 740°C at a heating rate of 2°C / min, and sinter in a nitrogen atmosphere at this temperature for 8h to obtain the lithium manganese iron phosphate material.

[0099] Comparative Example 9

[0100] The lithium iron manganese phosphate LiMn provided in this comparative example 0.6 Fe 0.4 The PO4 positive electrode material is Scholander-LMFP64 purchased on the market.

[0101] Let 1.1*m3-9*m1-2*m2-0.6*m4 be M, and the relationship between m1-m4 and M is shown in Table 1:

[0102] Table 1

[0103]

[0104]

[0105] Test Case

[0106] The compaction density of the phosphate positive electrode material prepared in each embodiment and comparative example was tested. The test method was determined in accordance with the provisions of Appendix L of GB / T24533-2019. The results are shown in Table 2.

[0107] The specific surface area of ​​the phosphate positive electrode material prepared in each embodiment and comparative example was tested. The test method was carried out in accordance with the provisions of GB / T13390-2008. The results are shown in Table 2.

[0108] Table 2 Compacted density of phosphate positive electrode materials in various embodiments and comparative examples

[0109]

[0110]

[0111] The power cycle performance test includes the following steps:

[0112] The cycle performance of the lithium-ion battery made of the phosphate positive electrode material prepared in each embodiment and comparative example was tested. The preparation method of the lithium-ion battery is as follows: the phosphate positive electrode material, the conductive agent CNT and the adhesive PVDF are mixed in a solvent (NMP) at a fixed mass ratio of 80:15:5, and then evenly coated on the current collector aluminum foil after stirring, pressed and dried, and then cut into a disc with a diameter of 12 mm, and finally the positive electrode sheet of the button battery is obtained. The lithium sheet (thickness of 0.6 mm) is used as the negative electrode, and fluoroethylene carbonate, dimethyl carbonate and ethylene carbonate (volume ratio of 10:45:45) containing 1 mol / L LiPF6 are used as the electrolyte, and the purchased polypropylene film is cut and used as a diaphragm, and the button battery is assembled in the argon atmosphere of the glove box.

[0113] The test method is as follows: set the test voltage to 2.5-4.3V, and strictly maintain the test temperature at 25°C. Use the battery test system (LAND CT2001A) to test the first discharge gram capacity of the button battery at 0.1C and the cycle performance at 1C, and calculate the capacity retention rate after 200 cycles at 1C. The results are shown in Table 3.

[0114] Table 3

[0115]

[0116] It can be seen from the data in Tables 1, 2 and 3 that only when the first slurry, the second slurry, the third slurry and the fourth slurry of the phosphate positive electrode material simultaneously satisfy the particle size relationship and the mass percentage relationship, the prepared phosphate positive electrode material can obtain a high compaction density (greater than or equal to 2.46 g / cm 3 ), specific capacity (first discharge specific capacity is greater than or equal to 152.38 mAh / g) and cycle stability (200-cycle capacity retention rate is greater than or equal to 89.06%).

[0117] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a phosphate positive electrode material, characterized in that: The steps include: Mixing raw materials and solvent to form an initial slurry; grouping the initial slurry and refining them to obtain a first slurry, a second slurry, a third slurry, and a fourth slurry; wherein the raw materials include a metal source and a phosphorus source; The first slurry, the second slurry, the third slurry and the fourth slurry are mixed to obtain a mixed slurry, and then dried and sintered to obtain the phosphate positive electrode material; Among them, the particle size D1 of the first slurry 50 20-80nm; the particle size D2 of the second slurry 50 100-150nm; the particle size D3 of the third slurry 50 180-350nm; the particle size D4 of the fourth slurry 50 400-500nm; The first slurry accounts for 3-5% of the mixed slurry by mass m1, the second slurry accounts for 10-12% of the mixed slurry by mass m2, the third slurry accounts for 56-65% of the mixed slurry by mass m3, and the fourth slurry accounts for 20-27% of the mixed slurry by mass m4; and the mass percentages of each slurry satisfy the following relationship: m1+m2+m3+m4=100%.

2. The preparation method according to claim 1, characterized in that: The raw material also includes a carbon source; Preferably, the metal source includes a transition metal source and an alkali metal source; Preferably, the transition metal source comprises an iron source; Preferably, the transition metal source includes an iron source and a manganese source; Preferably, the alkali metal source is selected from a lithium source or a sodium source.

3. The preparation method according to claim 1 or 2, characterized in that: The mass percentage of each slurry satisfies the following relationship: -0.1≤1.1*m3-9*m1-2*m2-0.6*m4≤0.12; Further preferably, the mass percentage of each slurry satisfies the following relationship: -0.05≤1.1*m3-9*m1-2*m2-0.6*m4≤0.

05.

4. The preparation method according to claim 2, characterized in that: The phosphorus source is selected from at least one of iron phosphate, lithium dihydrogen phosphate, lithium phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid; Preferably, the iron source is selected from at least one of ferric phosphate, ferric oxide, ferrous oxalate, iron powder, and ferric manganese nitrate; Preferably, the manganese source is selected from at least one of manganese carbonate, manganese oxalate, manganous acetate, manganese dioxide, manganese hydroxide, manganese sulfate, and manganese tetraoxide; Preferably, the carbon source is selected from at least one of acetylene black, Ketjen black, graphene, glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, and polyaniline; Preferably, the lithium source is selected from at least one of lithium dihydrogen phosphate, lithium nitrate, lithium carbonate, lithium phosphate, lithium hydroxide or lithium acetate; Preferably, the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium acetate, sodium citrate and sodium sulfate; Preferably, the mass ratio of the carbon element in the carbon source to the phosphorus element in the phosphorus source in the raw material is (0.05-0.7:1).

5. The preparation method according to claim 1, characterized in that: The concentration of raw materials in the initial slurry is 10-70g / L; Preferably, the solvent is selected from deionized water, ethanol or methanol.

6. The preparation method according to claim 1, characterized in that: The sintering temperature is 400-900°C and the sintering time is 4-30h; Preferably, the heating rate during the sintering process is 1-5°C / min.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the first slurry, the second slurry, the third slurry and the fourth slurry in the mixed slurry is 3:12:60:

25.

8. The preparation method according to claim 1, characterized in that: The phosphate positive electrode material is lithium iron manganese phosphate, lithium iron phosphate, sodium iron phosphate or sodium iron pyrophosphate.

9. A phosphate positive electrode material, characterized in that: The invention comprises a phosphate positive electrode material prepared by the preparation method described in any one of claims 1 to 8.

10. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet is made of the phosphate positive electrode material according to claim 9.